The Chinese Belt and Road Initiative from the Polish Perspective - Dominika Choros\'‑Mrozowska (Comparative Economic Research. Central and Eastern Europe, 2019)
China announced its initiative of the so-called New Silk Road project for the first time in 2013. Although its extent, concept or even its current name (The Belt and Road Initiative, BRI) have changed on a number of occasions since then, it cannot be denied that this is one of the most important challenges currently being undertaken in the world. The countries of Central and Eastern Europe, of which Poland is a part, may have a significant meaning in this concept due to their strategic location. The countries of this region began their co-operation with China under the so-called "16 + 1" format, and this took place prior to the announcement of the BRI. This opens up new perspectives for Polish-Chinese trade relations in respect of the BRI initiative and the "16 + 1" platform. The aim of this study is therefore to present the most important effects of the conducted research, the assumption of which was the comprehensive identification of the Chinese BRI initiative and the consequences of its implementation for Polish-Chinese trade relations. The presented analysis assumes that BRI will have a significant impact on Polish-Chinese trade patterns. This is particularly important in the context of the huge trade deficit that Poland has been recording for years in its trade with China as well as the deepening asymmetry, which has been characteristic of the exchange.
Keywords: F00; F10; F13; 330; Belt and Road Initiative; "16 + 1" platform; import; export; trade deficit; FDI